Beispiel Nr: 04
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 9x -2y =1\\ -3x -3y = -7 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 9 x -2 y =1\\ II \qquad -3 x -3 y = -7 \\ \text{I nach x auflösen}\\ 9 x -2 y =1 \\ 9 x -2 y =1 \qquad /+2 y\\ 9 x =1 +2 y \qquad /:9 \\ x =\frac{1}{9} +\frac{2}{9} y \\ \text{I in II}\\ -3 (\frac{1}{9} +\frac{2}{9} y ) + -3 y = -7 \\ -\frac{1}{3} -\frac{2}{3} y -3 y = -7 \qquad / -\left(-\frac{1}{3}\right) \\ -\frac{2}{3} y -3 y = -7 -\left(-\frac{1}{3}\right) \\ -3\frac{2}{3} y = -6\frac{2}{3} \qquad /:\left(-3\frac{2}{3}\right) \\ y = \frac{-6\frac{2}{3}}{-3\frac{2}{3}} \\ y=1\frac{9}{11} \\ x =\frac{1}{9} +\frac{2}{9} y \\ x =\frac{1}{9} +\frac{2}{9} \cdot 1\frac{9}{11} \\ x=\frac{17}{33} \\ L=\{\frac{17}{33}/1\frac{9}{11}\} \end{array} & \begin{array}{l} I \qquad 9 x -2 y =1\\ II \qquad -3 x -3 y = -7 \\ \text{I nach y auflösen}\\ 9 x -2 y =1 \\ 9 x -2 y =1 \qquad /-9 x\\ -2 y =1 -9x \qquad /:\left(-2\right) \\ y =-\frac{1}{2} +4\frac{1}{2}x \\ \text{I in II}\\ -3x + -3(-\frac{1}{2} +4\frac{1}{2} x ) = -7 \\ 1\frac{1}{2} -13\frac{1}{2} x -3 x = -7 \qquad / -1\frac{1}{2} \\ -13\frac{1}{2} x -3 x = -7 -1\frac{1}{2} \\ -16\frac{1}{2} x = -8\frac{1}{2} \qquad /:\left(-16\frac{1}{2}\right) \\ x = \frac{-8\frac{1}{2}}{-16\frac{1}{2}} \\ x=\frac{17}{33} \\ y =-\frac{1}{2} +4\frac{1}{2} x \\ y =-\frac{1}{2} +4\frac{1}{2} \cdot \frac{17}{33} \\ y=1\frac{9}{11} \\ L=\{\frac{17}{33}/1\frac{9}{11}\} \end{array} \end{array} $